The Role of Gut Bacteria and Fungi in Alcohol-Associated Liver Disease - Chen, Liuying; Zhu, Yixin; Hou, Xiaohua; Yang, Ling; Chu, Huikuan (Frontiers in Medicine, 2022)
Cirrhosis and liver cancer caused by alcohol-associated liver disease (ALD) are serious threats to people's health. In addition to hepatic cell apoptosis and liver inflammation caused by oxidative stress during alcohol metabolism, intestinal microbiota disorders are also involved in the onset and development of ALD. Ethanol, including its’ oxidative and non-oxidative metabolites, together with dysbiosis-caused-inflammation, destroys the intestinal barrier. Changes of several microbial metabolites, such as bile acids, short-chain fatty acids, and amino acid, are closely associated with gut dysbiosis in ALD. The alcohol-caused dysbiosis can further influence intestinal barrier-related proteins such as mucin2, bile acid-related receptors, and aryl hydrocarbon receptor, and these abnormal changes also participate in the injury of the intestinal barrier and hepatic steatosis. Gut-derived bacteria, fungi, and their toxins such as lipopolysaccharide (LPS) and β-glucan translocate into the liver through the damaged intestinal barrier and promote the progression of inflammation and fibrosis of ALD. Thus, prevention of alcohol-induced disruption of intestinal permeability has a beneficial effect on ALD. Currently, multiple therapeutic treatments have been applied to restore the gut microbiota of ALD patients. Fecal microbial transplantation, probiotics, antibiotics, and many other elements has already shown their ability of restoring the gut microbiota. Targeted approaches such as using bacteriophages to remove cytolytic E. faecalis, and supplement with Lactobacillus, Bifidobacterium or boulardii are also powerful therapeutic options for ALD.